Esterification of Cinnamic Acid using Menthol and its Activity as Lowering Glucose Levels using Anthrone Sulfate - yuliana purwaningsih; Mighfar Syukur; Wulandari Wulandari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
This study aimed to synthesize menthyl cinnamate and its activity as a glucose-lowering agent. Synthesis of methyl cinnamate using Fischer esterification of cinnamic acid and menthol with sulfuric acid as a catalyst using reflux at a temperature of 60oC with a synthesis time variation of 4,5 and 6 hours. Identification of synthesis results using FTIR spectrophotometry and GC-MS. Glucose lowering activity of the synthesis product using anthrone sulfate. The synthesized compound was a yellow oil liquid with a sweet fruity aroma typical of cinnamic esters with a yield % of 95.83%, 96.38, and 91.79%, respectively, at 4, 5, and 6 hours. The synthesized product was soluble in nonpolar solvents. Analysis by FTIR showed several functional groups such as C=O, C=C, C-O, and C-H aliphatic. Analysis of the synthesis results with GC-MS showed a retention time of 18.38 minutes for menthyl cinnamate with m/z = 286. Test with anthrone sulfate gave an optimum concentration of 300 ppm with a % decrease in the glucose of 48.62%. Based on these results, it can be concluded that menthyl cinnamate can be synthesized with optimum yield in 5 hours and has potential as an antidiabetic agent.